2016
DOI: 10.1093/cid/ciw599
|View full text |Cite
|
Sign up to set email alerts
|

Expression of C-Reactive Protein and Serum Amyloid A in Early to Late Manifestations of Lyme Disease

Abstract: Background. Infection with Borrelia burgdorferi, the causative agent of Lyme disease, triggers host immune responses that affect the clinical outcome and are a source of biomarkers with diagnostic utility. Although adaptive immunity to B. burgdorferi has been extensively characterized, considerably less information is available about the development of innate acute-phase responses in Lyme disease. Our aim in this study was to evaluate the expression of C-reactive protein (CRP) and serum amyloid A (SAA), the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 26 publications
2
32
0
2
Order By: Relevance
“…This is important in order to rule out other symptom causes such as severe anemia, liver, kidney or other metabolic conditions such as diabetes, or other inflammatory or neoplastic conditions. Mild elevations in C-reactive protein have been reported in PTLD (106), however moderate to severe elevations in the erythrocyte sedimentation rate or C-reactive protein are distinctly unusual and should prompt evaluation of another infectious, neoplastic, or autoimmune condition, such as polymyalgia rheumatica.…”
Section: Laboratory and Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…This is important in order to rule out other symptom causes such as severe anemia, liver, kidney or other metabolic conditions such as diabetes, or other inflammatory or neoplastic conditions. Mild elevations in C-reactive protein have been reported in PTLD (106), however moderate to severe elevations in the erythrocyte sedimentation rate or C-reactive protein are distinctly unusual and should prompt evaluation of another infectious, neoplastic, or autoimmune condition, such as polymyalgia rheumatica.…”
Section: Laboratory and Imagingmentioning
confidence: 99%
“…Investigation into the role of an ongoing immune response in the symptomatology of patients with persistent symptoms is in its earliest stages. A handful of studies have suggested that inflammatory markers such as C-reactive protein, as well as immune mediators such as CCL19 and IL-23, remain elevated for months after completion of antibiotic therapy among patients with persistent symptoms (47,48,106). Anti-neural antibody reactivity is higher in those with persistent symptoms, even among those who are seronegative, compared to those who returned to health after treatment for Lyme disease (149).…”
Section: Etiologymentioning
confidence: 99%
“…Unfortunately, there is currently no good test, genetic or otherwise, to identify patients at higher risk for developing PTLDS a priori who may benefit from more aggressive therapy with intravenous antibiotics. There are several markers reported that may be related to PTLDS, such as increased immune response to VlsE membrane-proximal epitopes in PTLDS patients (39), innate acute C-reactive protein (40), T-cell chemokine CCL19 (41), and greater frequency of the TLR1-1805GG polymorphism (42). It seems possible that a combination of several markers may provide a basis for identifying high-risk patients for PTLDS.…”
Section: Discussionmentioning
confidence: 99%
“…To the Editor-We thank Naktin for his letter [1] regarding our recently published study in Clinical Infectious Diseases [2] in which we examined the expression of acute phase response proteins in patients with various manifestations of Lyme disease. Naktin expressed concern over the extrapolation that was made regarding the level of anti-Borrelia burgdorferi antibody based on the optical density (OD) signal measured in the enzyme-linked immunosorbent assay.…”
Section: Reply To Naktinmentioning
confidence: 99%